Mechanosensitive lncRNA H19 promotes chondrocyte autophagy, but not pyroptosis, by targeting miR-148a in post-traumatic osteoarthritis - Xuchang Zhou; Hong Cao; Tao Liao; Weizhong Hua; Ruobing Zhao; Dongxue Wang; Huili Deng; Yajing Yang; ShengYao Liu; Guoxin Ni (Non-coding RNA Research)
Objective: Investigating whether mechanosensitive lncRNA H19 can directly target miR-148a to alleviate cartilage damage in post-traumatic osteoarthritis (PTOA). Methods: Thirty-two female rats were randomly divided into four groups: Sham-operated group (Sham group, n = 8), treadmill running group (R group, n = 8), anterior cruciate ligament transection (ACLT) group (ACLT group, n = 8), and ACLT + treadmill running group (ACLT + R group, n = 8). Histological evaluation was performed to observe the pathological changes in the cartilage of the rat knee. Micro-CT was performed to detect the bone morphological changes in the subchondral bone. RT-qPCR and Western-Blot were performed to detect changes in mRNA and protein levels of metabolic and inflammatory factors as well as changes in the expression of lncRNA H19 and miR-148a in cartilage. The Flexcell 5000™ Tension System was used to further validate that lncRNA H19 has mechanosensitivity in vitro. Finally, cell transfection techniques were used to knock down the expression of lncRNA H19 in chondrocytes to validate the regulatory role of lncRNA H19/miR-148a in cartilage metabolism. Results: ACLT combined with treadmill running aggravated the abnormal hyperplasia of subchondral bone in the lateral tibial plateau of the rat knee joint, disturbed the balance of cartilage metabolism, induced cartilage inflammatory response and chondrocyte pyroptosis, which eventually led to cartilage damage and PTOA. Importantly, we found that the expression of lncRNA H19 was significantly downregulated in the cartilage of the ACLT + R group. Bioinformatics analysis revealed that miR-148a may be a direct target of lncRNA H19. Subsequently, we focused on the mechanosensitive of lncRNA H19. Subsequently, moderate-intensity mechanical tension stress reversed the expression of lncRNA H19 and autophagy-related factors in inflammatory chondrocytes, while miR-148a showed an opposite expression trend, demonstrating that mechanosensitive lncRNA H19 may be involved in regulating the chondrocyte inflammatory response by targeting miR-148a and activating autophagy. Cell transfection experiments revealed that lncRNA H19 knockdown upregulated miR-148a expression and significantly inhibited the autophagy level of chondrocytes without significant alteration of chondrocyte pyroptosis, which in turn exacerbated the inflammatory response of chondrocytes. Conclusions: Mechanosensitive lncRNA H19 can promote chondrocyte autophagy rather than pyroptosis by targeting miR-148a, thus alleviating cartilage damage in PTOA. LncRNA H19 may be a potential therapeutic target for PTOA.